1995
DOI: 10.1007/bf02740673
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining the neuronal phenotype after injury in the adult CNS

Abstract: Multiple genetic and epigenetic events determine neuronal phenotype during nervous system development. After the mature mammalian neuronal phenotype has been determined it is usually static for the remainder of life, unless an injury or degenerative event occurs. Injured neurons may suffer one of three potential fates: death, persistent atrophy, or recovery. The ability of an injured adult neuron to recover from injury in adulthood may be determined by events that also influence neuronal phenotype during devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 95 publications
0
12
0
Order By: Relevance
“…As concerns grafted embryonic neurons, it would be optimum to induce the expression of neuroprotective molecules only for the period during which the grafted neurons settle and integrate in the host cord, differentiate to a limited extent, establish interaction with the host cord, and extend their axons to the target (Tuszynski and Gage, 1995;Nakahara et al, 1996). This period is estimated as about 8-10 weeks for spinal cord grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As concerns grafted embryonic neurons, it would be optimum to induce the expression of neuroprotective molecules only for the period during which the grafted neurons settle and integrate in the host cord, differentiate to a limited extent, establish interaction with the host cord, and extend their axons to the target (Tuszynski and Gage, 1995;Nakahara et al, 1996). This period is estimated as about 8-10 weeks for spinal cord grafts.…”
Section: Discussionmentioning
confidence: 99%
“…N EURONS THAT ARE SEVERELY DAMAGED during development or adult life can be rescued by various methods, including the delivery of neuroprotective substances (Tuszynski and Gage, 1995;Fawcett, 1998). The various virus-based systems have been found to be superior over other approaches as their use produces the required effects only in the targeted cells, without systemic effects.…”
Section: Introductionmentioning
confidence: 99%
“…The optic nerve as a part of CNS, damage to which is difficult to regenerate [20,21,22,23]. RGCs axons form the optic nerve, injury of which is one of the causes of visual loss.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most prominently studied neurotrophic factors in the CNS are NGF, brain-derived neurotrophic factor (BDNF), glial cell line derived neurotrophic factor (GDNF), and insulin-like growth factor 1 (IGF-1). These neurotrophins and their receptors are highly expressed in both the human and rodent CNS (Adem et al, 1989, Kawamoto et al, 2000, Lu et al, 1989, Tang et al, 2010) and research has demonstrated critical roles for these factors in the growth and stabilization of dendritic spines, synaptic plasticity, long-term potentiation, survival of neurons and glia, and therefore unsurprisingly learning and memory (for review see (Vicario-Abejón et al, 2002, Arancio and Chao, 2007, Park and Poo, 2013, Russo et al, 2005, Tuszynski and Gage, 1995). …”
Section: Neurotrophic Factors In Cns Disorders and Potential Therapeutimentioning
confidence: 99%